Effects of Climate Change on Grassland Biodiversity and Productivity - Gianni Bellocchi; Catherine Picon-Cochard (Agronomy, 2021)
Associated with livestock farming, grasslands with a high diversity of plant species are at the core of low-input fodder production worldwide [...]